Inclusive education: Bridging the gap between online and face-to-face teaching modalities - Morrar, Najiba; Abdul Majeed, Ayman; Qassrawi, Rania (Edelweiss Applied Science and Technology, 2024)
In the post-COVID-19 era, higher education institutions worldwide are increasingly adopting a blend of online and face-to-face teaching. The pandemic-induced shift to remote learning has prompted concerns about the inclusivity of online education compared to traditional classroom settings. This study aimed to evaluate the principles of inclusive education across both modalities, drawing on the experiences of (85) students from Birzeit University during the second semester of the 2022-2023 academic year. Three courses were examined: Scientific Research Methodology, Applied Action Research in Inclusive Education and Special Education, and Advanced English Language. Following a qualitative approach and descriptive analysis, the study collected data through students’ reflective journals, in which they described their experiences with both teaching modes. The analysis was guided by UNESCO’s 2017 inclusive education framework categorized into four domains: diversity and alignment in teaching methods, active participation and interaction, accessibility of educational materials and equity and justice. Findings indicated that although students generally perceived face-to-face teaching as more inclusive, there are potential benefits of a blended approach were also acknowledged, suggesting that combining online and face-to-face methods could enhance inclusivity. The study recommended a blended teaching approach to improve accessibility and flexibility, providing options that accommodate students’ diverse needs, preferences and impairments. Additionally, it emphasized the importance of equitable access to technology and the internet to overcome barriers in hybrid learning, ensuring that no student is left behind.